2007
DOI: 10.2320/matertrans.48.445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nb Content on Martensitic Transformation Temperatures and Mechanical Properties of Ti-Ni-Nb Shape Memory Alloys for Pipe Joint Applications

Abstract: Several Ti-Ni-Nb shape memory alloys (SMAs) with various Nb contents (0$15 mol%) or Ni/Ti atomic ratios (1:0$1:1) were tested to investigate the martensitic transformation temperatures and mechanical properties. The martensitic transformation temperatures (M s , M f , A s and A f ) of the solution-treated Ti-Ni-Nb alloys at 1173 K for 300 seconds with Ni/Ti ratio of 1.0 decrease with increasing the Nb content. These transformation temperatures also depend on the Ni/Ti ratio, heat treatment condition and cold w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…For both Ti 50 Ni 50-x Nb x and Ti 50-x/2 Ni 50-x/2 Nb x alloys (to which our alloy belongs), M s decreases by 20-40 C for a Nb content of 3 at.%. Uchida et al 32 reported a decrease in transformation temperature of $30 C after adding 3 at.% Nb to equiatomic NiTi produced by vacuum induction melting. This is in general agreement with the decline of M s by 23 C from NT0 to NTN0 and by 36 C from NT40 to NTN40 (Table II).…”
Section: Phase Transformationsmentioning
confidence: 98%
See 2 more Smart Citations
“…For both Ti 50 Ni 50-x Nb x and Ti 50-x/2 Ni 50-x/2 Nb x alloys (to which our alloy belongs), M s decreases by 20-40 C for a Nb content of 3 at.%. Uchida et al 32 reported a decrease in transformation temperature of $30 C after adding 3 at.% Nb to equiatomic NiTi produced by vacuum induction melting. This is in general agreement with the decline of M s by 23 C from NT0 to NTN0 and by 36 C from NT40 to NTN40 (Table II).…”
Section: Phase Transformationsmentioning
confidence: 98%
“…Also, it is known that the addition of Nb increases the local Ni/Ti ratio in the NiTi-rich B2 phase responsible for the recovery effect, and increases the proportion of the Nb-rich phase, which resists transformation of the B2 phase in the eutectic. 32,43 Therefore, transformation becomes more difficult, and transformation temperatures are decreased. Piao et al 43 studied the martensitic start temperature (M s ) in NiTi-Nb arc-melted alloys.…”
Section: Phase Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TiNiNbSMA has a high transformation temperature hysteresis and has thus been used in pipe joints and similar applications. Uchida et al (2007) manufactured the alloy in a high-frequency induction vacuum furnace and prepared two samples: One sample with Ni/Ti atomic ratio equal to 1, and Nb concentration between 0 and 15 mol%, whereas another sample contains Nb concentration 6 mol%, and the Ni/Ti ratio was changed from 1.025 to 1.1. Transformation temperature decreased with increasing Nb content in the first sample, and a huge deviation was recorded with Nb being 12 mol%, the second sample having Ni/Ti ratio is 1.088.…”
Section: Effect Of the Additional Elementmentioning
confidence: 99%
“…In particular, when the soft β-Nb phase in the NiTiNb SMA suffers from plastic deformation, the relaxation of elastic strain in the martensite interface contributes to lowering the driving force of reverse martensite transformation and, hence, facilitating the stability of martensite [9]. Therefore, NiTiNb SMA has been a perfect candidate for pipe coupling because the large phase transformation temperature hysteresis plays a predominant role in guaranteeing the reliability of pipe coupling in engineering applications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%